Factors Affecting Mortality of Sepsis Patients in General Hospital Dr. M. Djamil Padang - Aribowo, Kornelis; Sari, Wiwi Monica (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2024)
Background: The high sepsis mortality rate is a significant problem that must be managed properly and comprehensively. Studies showed 30% mortality due to sepsis, 50% for severe sepsis, and 80% for sepsis shock. Data in Indonesia showed that 30.29% of sepsis patients were admitted, and 11.56% to 49% died. Vitamin D deficiency is associated with an increased risk of infection in sepsis.Objective:This study aims to determine the factors that play a role in the death of sepsis patients.Methods: This study used a cross-sectional analytic design. Data were tak-en from 42 patients who died from sepsis in the Intensive care unit of Dr. M. Djamil Padang Hospital from July 2022 to Sep-tember 2022. Patients were previously checked for vitamin D levels—data analysis using the Man Whitney test.Results:The average age of sepsis patients is 56 years old, female (59.9%), vitamin D deficiency (82.5%), obesity (64.3%), most comorbid with chronic kidney injury (CKD) (16.7%). Sepsis pa-tients who died of vitamin D deficiency had a mean Hb of 11.5 g/dl; leukocytosis (14.490/mm3), thrombocytopenia (225.000/mm3), hypoalbumin (2.4 g/dl) and high risk to sepsis based on procalcitonin levels (15.47 ng/ml). There was no sta-tistically significant relationship to the laboratory results (pValue>0.05).Conclusion:Vitamin D deficiency, female, obesity, CKD, thrombocytopenia, and hypoalbumin increase the mortality risk of sepsis patients in the intensive care Unit. The importance of recognizing demo-graphic and laboratory risk factors helps clinicians in preventing sepsis mortality.Background: The high sepsis mortality rate is a significant problem that must be managed properly and comprehensively. Studies showed 30% mortality due to sepsis, 50% for severe sepsis, and 80% for sepsis shock. Data in Indonesia showed that 30.29% of sepsis patients were admitted, and 11.56% to 49% died. Vitamin D deficiency is associated with an increased risk of infection in sepsis.Objective:This study aims to determine the factors that play a role in the death of sepsis patients.Methods: This study used a cross-sectional analytic design. Data were tak-en from 42 patients who died from sepsis in the Intensive care unit of Dr. M. Djamil Padang Hospital from July 2022 to Sep-tember 2022. Patients were previously checked for vitamin D levels—data analysis using the Man Whitney test.Results:The average age of sepsis patients is 56 years old, female (59.9%), vitamin D deficiency (82.5%), obesity (64.3%), most comorbid with chronic kidney injury (CKD) (16.7%). Sepsis pa-tients who died of vitamin D deficiency had a mean Hb of 11.5 g/dl; leukocytosis (14.490/mm3), thrombocytopenia (225.000/mm3), hypoalbumin (2.4 g/dl) and high risk to sepsis based on procalcitonin levels (15.47 ng/ml). There was no sta-tistically significant relationship to the laboratory results (pValue>0.05).Conclusion:Vitamin D deficiency, female, obesity, CKD, thrombocytopenia, and hypoalbumin increase the mortality risk of sepsis patients in the intensive care Unit. The importance of recognizing demo-graphic and laboratory risk factors helps clinicians in preventing sepsis mortality.